A textual analysis of MTV exit's Davao roadshow advocacy videos - Fuentes, Sarah Jane G.
A textual analysis of MTV exit?s Davao Roadshow advocacy videos is an analysis discussing the narrative components of the story (setup, compilation, and resolution) as used in the videos of MTV Exit?s campaign to encourage, portray and convey the issues of human trafficking. The study looks at the three main videos namely, intersection, an animated short film created in 2009; Traffic a documentary hosted by Christian Bautista (2008); and enslaved a documentary hosted by Dingdong Dantes (2011). In analyzing the content of these advocacy videos, a qualitative textual analysis specifically on Narrative and Semiotic Theories was employed. The analysis includes the discussion of the narrative elements and the narrative codes: proairetic code (ACT); hermeneutic code (HER); symbolic code (SYM); semantic code (SEM); and cultural code (REF) as used by the filmmakers in portraying the messages in the videos. While the data gathering and procedures of this study made use of both the Centre de Liason del?Enseignement et des Medias d?Information (CLEMI) and Michael Rabiger?s proposed methods: Film Aesthetic Questionnaire (FAQ) and Film Analysis Form (FAF). The result of this study shows that the issues of human trafficking was well depicted in the three advocacy videos of MTV exit, all showing the same message- the trafficking chain. The used of the narrative codes by the filmmaker were evident in portraying the message in each scenes and sequences of the story component (especially the ACT, HER, and SEM). The result also revealed that the three are common topics that emerge in the videos especially in the two documentaries such as the introduction of human trafficking and exploitation; the trafficking chain; the characters and their agendas; the tactics of the traffickers; debt bondage; reasons for widespread trafficking; the rehabilitation; recovery of the victims; and the persuasive message provided towards the end.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts